Augmented reality media of the human reproductive system for class XI high school students - Putri, Husmayani Muny; Pertiwi, Kartika Ratna (JURNAL BIOEDUKATIKA, 2022)
Learning today is closely related to digital technology, especially during Covid-19. The form of use of digital technology is the variety of products being developed. Still, almost no media can meet all age levels, and there are differences in student abilities, so careful design is needed. In biology learning material on the human reproductive system, it is known that the learning completeness score is low (46.2%). The reason is that this material requires good concept visualization while the existing media is minimal. Teachers and students need media that can visualize material well and can be accessed via smartphone. This research aims to develop Augmented Reality (AR) media on human reproductive system material. This research uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Data collection was carried out through expert validation and limited trials. The material expert validation result was 100%, and the media expert validation result was 95% (very good category). The teacher assessment result was 92%, and the student response was 83.5% (very good category). Based on these results, it is known that the AR media developed is suitable for use in learning.